2004
DOI: 10.1161/01.cir.0000149714.31471.fd
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Analysis of the Anatomy of the Left Atrium and the Esophagus

Abstract: Background-During left atrial (LA) catheter ablation, an atrioesophageal fistula can develop as a result of thermal injury of the esophagus during ablation along the posterior LA. No in vivo studies have examined the relationship of the esophagus to the LA. The purpose of this study was to describe the topographic anatomy of the esophagus and the posterior LA by use of CT. Methods and Results-A helical CT scan of the chest with 3D reconstruction was performed in 50 patients (mean age, 54Ϯ11 years) with atrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
1
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(201 citation statements)
references
References 22 publications
10
178
1
12
Order By: Relevance
“…19,20 The VN and its branches innervate most of the UGI system. The right and left VN descend alongside the esophagus into the abdomen, and their course in the posterior mediastinum is variable.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The VN and its branches innervate most of the UGI system. The right and left VN descend alongside the esophagus into the abdomen, and their course in the posterior mediastinum is variable.…”
Section: Discussionmentioning
confidence: 99%
“…45 To avoid an atrio-esophageal fistula, understanding the relationship between the esophagus and LA is paramount. Lenola et al 46 reported the topographic anatomy of the esophagus and posterior LA by using a 16-row multidetector CT scanner in patients with AF undergoing a percutaneous catheter ablation procedure. They identified that the esophagus and posterior LA were in close contact over a large area with an intervening fat layer of 0.9±0.2 mm, suggesting the potential risk of heat injury to the esophagus.…”
Section: Atrio-esophageal Fistulamentioning
confidence: 99%
“…7 In the present study, direct contact of the esophagus with the LAPW was demonstrated in 14 of 24 patients (58%) and the difference might be related to the methodology used, in which the geometry constructed in our study represented the endocardial surface or lumen of the organs and the wall thickness of the LAPW and esophagus were not taken into account, whereas the outer surfaces of the esophagus and LAPW are demonstrated in the CT image. Sanchez-Quintana et al, however, reported that the esophageal wall was a distance of over 5 mm from the endocardium of the LAPW in the analysis of their specimens.…”
Section: Relationship Between the Esophagus And The Lapwmentioning
confidence: 54%
“…5,6 In all, recognition of the location of the esophagus relative to the LAPW is an inevitable initial step. Although preprocedural computed tomography (CT) and magnetic resonance imaging (MRI) have been reported as useful for recognizing this relationship, 7 the esophagus is mobile and thus the location at the time of imaging might not be the same as that during the ablation procedure, 8 so real-time 3-dimensional (D) visualization of the 2 organs during the RF ablation has been anticipated.…”
mentioning
confidence: 99%